PERANAN KOMUNIKASI ORGANISASI KARANG TARUNA GUYUB RUKUN DALAM MENINGKATKAN MORAL PEMUDA DI DUSUN SUMBER CANGKRING KELURAHAN KEYONGAN KECAMATAN NOGOSARI KABUPATEN BOYOLALI - Setiyarini, Yuni; Hindra H, Nurnawati; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The conclusion of this research shows that the Karang Taruna GuyubRukun Dusun Sumber Cangkring takes an approach through organizationalcommunication towards teenagers in Dusun Sumber Cangkring. This approachtakes the form of an invitation to participate in religious and social activities.From this activity, the youth who are members of Karang Taruna Guyub RukunDusun Sumber Cangkring get examples of good behavior. Suggestions for theSumber Cangkring Hamlet Youth Organization: (1) To the Sumber CangkringDusun Rukun Guyub Youth Organization to be able to optimize the performanceof members and administrators to be able to maintain social awareness,especially in terms of morality. (2) Efforts to improve grammar among the peopleof Sumber Cangkring hamlet. (3) Be more critical in terms of organizing andcommunicating.KEYWORD: Karang Taruna, Organizational Communication, Moral